A Comprehensive Review of Cellulose and Cellulose-Based Materials: Extraction, Modification, and Sustainable Applications - M. Madhushree; P. Vairavel; GT Mahesha; K. Subrahmanya Bhat (Journal of Natural Fibers)
Currently, the environmental crisis is one of the key issues that need to be addressed. Cellulose is one such material which can be used as it is abundant and eco-friendly. The production and use of cellulose-based materials generally have a lower environmental footprint compared to synthetic polymers. Cellulose is biocompatible, making it safe for medical and pharmaceutical uses. These materials are lightweight with fibrous structures that are well suited for use in paper and textile industries. Other advantages of these materials are availability from renewable plant sources, possible use of recycled materials, and lower production costs. In packaging, it is used for its eco-friendly and biodegradable nature. Such materials are also used in health care electronics, construction, and in printing industries. The food industry uses cellulose nanocomposites to enhance food quality and shelf life. These applications highlight cellulosic materials role in creating innovative and sustainable products across multiple industries. Chemical modifications of cellulose are an essential requirement to achieve optimal properties for specific applications. Furthermore, cellulosic nanomaterials are developing into newer areas with larger scope and greater economic value. This review covers the isolation of cellulose from various sources and the different modifications performed along with their applications.